The Effect of Industry Expertise, Familiarity Threat, and Workshops on Audit Judgment - Ricky Bryan D.P. Tampubolon (GLOBAL SCIENTS PUBLISHER, 2026)
Audit judgment is a crucial element in determining audit quality, yet it is influenced by various internal and external auditor factors. This study aims to analyze the effect of industry expertise, familiarity threat, and workshops on the audit judgment of external auditors in Jakarta. Primary data were collected through a survey of 135 senior external auditors with at least two years of work experience in audit firms. The research instrument was a questionnaire using a 5-point Likert scale, with each variable consisting of 10 statement items. The data were analyzed using multiple linear regression, supported by validity, reliability, and classical assumption tests. The results show that industry expertise and workshops have a significant positive effect on audit judgment, while familiarity threat has a significant negative effect. Simultaneously, the three variables significantly influence audit judgment, with an explanatory contribution of 33.1%. This study emphasizes the importance of industry expertise, auditor independence, and continuous learning through workshops in improving the quality of audit judgments, while also providing practical implications for the development of training policies and governance of the auditing profession in Indonesia.